Value Chain Structure Analysis as A Starting Point for Bamboo Enterprise Development: Lessons from Gunungkidul, Indonesia - Utomo, Marcellinus; Pieter, Levina; Siagian , Carmen M. (Forest and Society, 2021)
The economic contributions of rural enterprises in Indonesia are significant to support local people's livelihoods, although it remains at micro to medium levels. One small-scale enterprise, which remains understudied and receives little policy attention, is the bamboo enterprise. Gunungkidul Regency in Yogyakarta Special Province, a central region in Java Island, Indonesia, have many bamboo enterprises, creating various products that support some 6,500 jobs. This research is conducted as a case study of the Gunungkidul Regency. A value chain perspective was used to study three bamboo-based enterprises' value chain structure: kitchen utensils, bamboo toy handicraft, and chemically treated bamboo. The snowball concept was used until the data was saturated. In total, 86 respondents were interviewed. The traditional chain was dominant. The longest value chain and the highest number of actor levels were bamboo toy handicrafts, and the shortest and smallest actor level was the chemically treated bamboo. Most channels were in the toy handicraft chain in the production flow, then kitchen utensils, and chemically treated bamboo. The credit payment method is prevalent in financial flow, and trust has been widely established between actors. The information flow related to price was imbalanced. In each chain, collaboration in the raw material segment was weak. The lack of willingness of artisans to be more productive and the weak cooperation among artisans, coupled with the lack of support from the government seems to be obstacles to the development of bamboo as a small to medium enterprise in Gunungkidul